DC emulation of three bus transmission system - Narkhede, Anant; Fernandes, Brayan; Honyalkar, Dattatray; Raote, Chirag; Divya, M (2017 International Conference on Technological Advancements in Power and Energy ( TAP Energy), 2017)
There are many power system subjects in undergraduate level of Electrical Engineering. Experiments based on simulations are usually used to do power system analysis. In this project, an analog power system transmission lines is developed for the purpose of power flow computation. A three bus system is emulated using dc analog emulation method. Here power system network is represented using rectangular coordinates. Pi equivalent models of a lumped lossy transmission networks are considered throughout the study. This dc emulator is simulated using Multisim software [1] and tested for power flow analysis. Finally hardware for the system is implemented.